Evaluation of Echitamine, Ditamine and Echitenine for Anticataract Activity using in vitro cataract Model - Lokesh J Shetty (Journal of Applied Pharmaceutical Science, 2015)
The alkaloids such as echitamine, ditamine and echitenine were subjected for anti cataract activity using in vitro cataract model. Goat lenses were incubated in artificial aqueous humor containing 55 mM glucose with test alkaloids in different concentrations at room temperature for 72 h. Studied Biochemical parameters were sodium ion, potassium ion level and Na+-K+-ATPase activity. Glucose induced opacification of goat lens began 8-10 hrs after incubation and was complete in 72-80 hrs. Cataractous lenses treated with echitamine shown lower sodium ion, higher the potassium ion and higher Na+-K+-ATPase activity. Echitamine treated lens prevented formation and progress of cataract as evidenced by biochemical parameters and visual observation. Ditamine and echitenine were devoid of anti - cataract activity.
Keywords: Anti- cataract, Echitamine, ditamine, echitenine.